Developing global leaders through doctoral education (Revista Latino-Americana de Enfermagem, 2004)
Nursing leadership has become a major theme of discussions in many countries. The phenomenon is also present in nursing as the profession is redesigning and reinventing itself in all domains of practice. This paper discusses the development of global nursing leaders through doctoral education in the context of 21st century realities. Next, two meanings of global leadership of nursing are reviewed. Finally, doctoral education is focused by looking at worldviews and the challenges ahead in preparing global nursing leaders for the 21st century.